PENGARUH TERAPI FOOT MASSAGE TERHADAP KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Alina Dwita Anggarini; Sukesih, Sukesih; Sukarmin, Sukarmin (Nusantara Hasana Journal, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion and action. Uncontrolled blood sugar levels increase the risk of various complications. One complementary intervention that can help lower blood sugar levels is foot massage, a foot massage technique that involves pressure and manipulation to stimulate nerve points, improve blood circulation, activate the parasympathetic nervous system, and provide a relaxing effect. This study aims to determine the effect of foot massage on blood sugar levels in patients with T2DM. This study used a quasi-experimental design with a pre-test post-test control group design. A total of 40 respondents were divided into two groups: 20 respondents in the intervention group who were given foot massage for 10 consecutive days (15 minutes per session), and 20 respondents in the control group who only received health education. Blood sugar levels were measured before and after the intervention. In the intervention group, the average blood sugar level decreased by 14.90 mg/dL with a p value of 0.042 (p < 0.05), indicating a statistically significant decrease. In the control group, the average decrease was 27.15 mg/dL with a p value of 0.056 (p > 0.05), which means it is not significant. These results indicate that foot massage has a real effect in reducing blood sugar levels in patients with Type 2 DM. Foot massage is effectively used as a complementary therapy to help reduce blood sugar levels in patients with Type 2 DM. This therapy can be integrated into health services or done independently at home with the guidance of health workers.